Math, asked by rishika1088, 8 months ago


 \frac{tanq}{1 - cotq} +  \frac{cotq}{1 - tanq}   = 1 + secqcosecq

Answers

Answered by Anonymous
10

Solution:-

 \implies \rm \:  \dfrac{ \tan(q) }{1 -  \cot(q) }  +  \dfrac{ \cot(q) }{1 -  \tan(q) }

 \rm \implies \:    \dfrac{ \tan(q) }{1 -  \cot(q) }  +  \dfrac{ \cot(q ) }{1 -  \dfrac{1}{ \cot(q) } }

 \rm \implies \:  \dfrac{ \dfrac{1}{ \cot(q) } }{1 -  \cot(q) }  -  \dfrac{ \cot {}^{2} (q) }{1 -  \cot(q) }

 \rm \implies \:  \dfrac{ \dfrac{1}{ \cot(q)  } -  \cot {}^{2} (q)  }{1 -  \cot(q) }

 \rm \implies \:  \dfrac{1 -  \cot {}^{3} (q) }{ \cot(q) (1 -  \cot(q) )}

 \rm \implies \dfrac{(1 -  \cot(q) )(1 +  \cot(q) +  \cot {}^{2} (q)  )}{ \cot(q) (1 -  \cot(q) )}

\rm \implies \dfrac{ \cancel{(1 -  \cot(q) })(1 +  \cot(q) +  \cot {}^{2} (q)  )}{ \cot(q) \cancel{ (1 -  \cot(q)} )}

\rm \implies \dfrac{1 +  \cot(q) +  \cot {}^{2} (q)  }{ \cot(q) }

 \rm \:   \implies \dfrac{ \cot(q)  +  \csc {}^{2} (q) }{ \cot(q) }

 \rm \implies \:  \dfrac{ \cot(q) }{ \cot(q) }  +  \dfrac{ \csc {}^{2} (q) }{ \cot(q) }

 \rm \implies \: 1 +  \dfrac{ \dfrac{1}{ \sin {}^{2} (q) } }{ \dfrac{ \cos(q) }{ \sin(q) } }

 \rm \implies \: 1 +  \dfrac{1}{ \sin {}^{2} (q) }  \times  \dfrac{ \sin(q) }{ \cos(q) }

 \rm \implies \: 1 +  \dfrac{1}{ \sin(q) \cos(q)  }

 \rm \implies \: 1 +  \sec(q)  \csc(q)

hence proved

Answered by Anonymous
12

Solution :

\bf{\dfrac{tanq}{1 - cotq} + \dfrac{cotq}{1 - tanq} = 1 + secqcosecq}

From the above equation , we get :

  • LHS = \bf{\dfrac{tanq}{1 - cotq} + \dfrac{cotq}{1 - tanq}}

  • RHS = \bf{1 + secqcosecq} \\ \\

By solving the LHS , we get :

:\implies \bf{\dfrac{tanq}{1 - cotq} + \dfrac{cotq}{1 - tanq}} \\ \\ \\

We know that,

  • \bf{cot\:\theta = \dfrac{cos\theta}{sin\theta}}

  • \bf{cot\:\theta = \dfrac{cos\theta}{sin\theta}}

By substituting them in the equation , we get :

:\implies \bf{\dfrac{\dfrac{sinq}{cosq}}{1 - \dfrac{cosq}{sinq}} + \dfrac{\dfrac{\dfrac{cosq}{sinq}}{sinq}}{1 - \dfrac{sinq}{cosq}}} \\ \\ \\

:\implies \bf{\dfrac{\dfrac{sinq}{cosq}}{\dfrac{sinq - cosq}{sinq}} + \dfrac{\dfrac{cosq}{sinq}}{\dfrac{cosq - sinq}{cosq}}} \\ \\ \\

:\implies \bf{\dfrac{sinq}{cosq} \times \dfrac{sinq}{sinq - cosq} + \dfrac{cosq}{sinq} \times \dfrac{cosq}{cosq - sinq}} \\ \\ \\

:\implies \bf{\dfrac{sin^{2}q}{cosq(sinq - cosq)} + \dfrac{cos^{2}q}{sinq(cosq - sinq)}} \\ \\ \\

:\implies \bf{\dfrac{sin^{2}q}{cosq(sinq - cosq)} + \dfrac{cos^{2}q}{-sinq(sinq - cosq)}} \\ \\ \\

:\implies \bf{\dfrac{sin^{2}q}{cosq(sinq - cosq)} - \dfrac{cos^{2}q}{sinq(sinq - cosq)}} \\ \\ \\

:\implies \bf{\dfrac{sin^{2}q \times sinq - cos^{2}q \times cosq}{cosqsinq(sinq - cosq)}} \\ \\ \\

:\implies \bf{\dfrac{sin^{3}q - cos^{3}q}{cosqsinq(sinq - cosq)}} \\ \\ \\

:\implies \bf{\dfrac{sin^{3}q - cos^{3}q}{cosqsinq(sinq - cosq)}} \\ \\ \\

By using the identity, we get :

\bf{a^{3} - b^{3} = (a + b)(a^{2} + ab + b^{2}} \\ \\ \\

:\implies \bf{\dfrac{(sinq - cosq)(sin^{2}q + sinqcosq + cos^{q})}{cosqsinq(sinq - cosq)}} \\ \\ \\

:\implies \bf{\dfrac{(sinq - cosq)(sin^{2}q + sinqcosq + cos^{2}q)}{cosqsinq(sinq - cosq)}} \\ \\ \\

We know that ,

\bf{sin^{2}\theta + cos^{2}\theta = 1} \\ \\ \\

By substituting it in the equation , we get :

:\implies \bf{\dfrac{(sinq - cosq)(1 + sinqcosq)}{cosqsinq(sinq - cosq)}} \\ \\ \\

:\implies \bf{\dfrac{1 + sinqcosq}{cosqsinq}} \\ \\ \\

:\implies \bf{\dfrac{1 + sinqcosq}{cosqsinq}} \\ \\ \\

We know that,

  • \bf{cos\:\theta = \dfrac{1}{sec\theta}}

  • \bf{sin\:\theta = \dfrac{1}{cosec\theta}}

By substituting them in the equation , we get :

:\implies \bf{\dfrac{1 + \dfrac{1}{cosecq}\dfrac{1}{secq}}{\dfrac{1}{cosecq}\dfrac{1}{secq}}} \\ \\ \\

:\implies \bf{\dfrac{\dfrac{cosecqsecq + 1}{cosecqsecq}}{\dfrac{1}{cosecqsecq}}} \\ \\ \\

:\implies \bf{\dfrac{cosecqsecq + 1}{cosecqsecq} \times cosecqsecq} \\ \\ \\

:\implies \bf{cosecqsecq + 1} \\ \\ \\

\boxed{\therefore \bf{\dfrac{tanq}{1 - cotq} + \dfrac{cotq}{1 - tanq} = 1 + cosecqsecq}} \\ \\

Hence the LHS is 1 + cosecqsecq.

By putting the LHS and RHS together, we get :

:\implies \bf{1 + cosecqsecq = 1 + secqcosecq} \\ \\ \\

\boxed{\therefore \bf{\dfrac{tanq}{1 - cotq} + \dfrac{cotq}{1 - tanq} = 1 + secqcosecq}} \\ \\ \\

Hence proved !!

Similar questions